Antecedents of risky sexual practices among adolescents in military secondary schools in Oyo State, Nigeria (2015)
The crux of this study is to examine the predictive influence of peer pressure, sexual communication and parental influence as antecedents of risky sexual practices among adolescents in Oyo State military barracks secondary schools. Five hundred and one representative samples of adolescents with age range of 10 - 23 years and mean years of 17 ± 2.1 drawn using simple random sampling technique participated in the study. Respondents filled four standardized self-report scales. Results of the Pearson Product Moment Correlation analysis revealed that sexual communication and parental influence have inverse relationship (p<.05) with risky sexual practices. While a positive relationship exists between peer influence and risky sexual practices. The independent variables jointly accounted for 13.7 % of variance in the prediction of sexual practices of the respondents. The study underscores the need for tailored interventions that will involve parents in order to mitigate risky sexual practices for adolescents living in uniformed personnel neighbourhood.